Strategic plan for the working area development of fishing port for optimum services - Watung, Franky Y.; Masengi, K.W.A.; Dien, Heffry V. (AQUATIC SCIENCE & MANAGEMENT, 2016)
Title (Bahasa Indonesia): Rencana strategis pengembangan wilayah kerja pelabuhan perikanan untuk mendukung operasional pelabuhan secara optimal This study examines the working area development of fishing port to support optimal operations and services. The purpose of this study is to examine the working area coverage in  ​​the sea and land operations based on the ratio conditions of spatial utilization and sea operation in 2025, and to examine the implementation of IIU Fishing control in the fishing port and the carrying capacity of the port, based on the provisions of Ocean Fishery Port class. This study included primary and secondary data. The former was collected through interviews using questionnaires. The analysis applied SWOT, starting with identification of internal and external factors. Results found several development strategies including fishing port working area development of Bitung Fishing Port, fishermen’s residential area development, inter-sectoral coordination synergy, raw material availability for strengthening fisheries industries, sustainable and responsible fish resources management, human resources capacity building, law enforcement, information technology applications, standard dock development, and regulation consolidation. Penelitian ini mengkaji pengembangan wilayah kerja pelabuhan perikanan untuk mendukung operasional dan pelayanan pelabuhan secara optimal. Tujuan penelitian ini adalah mengkaji luas wilayah kerja operasional laut dan daratan berdasarkan kondisi rasio pemanfaatan ruang wilayah kerja dan operasional laut pada tahun 2025, mengkaji kondisi pelaksanaan pengendalian IIU Fishing di pelabuhan perikanan dan kondisi daya dukung dermaga, yang disesuaikan dengan ketentuan kelas Pelabuhan Perikanan Samudera. Data diperoleh dengan metode wawancara menggunakan kuisioner. Data sekunder juga digunakan dalam penelitian ini. Analisis data menggunakan analisis SWOT, dengan langkah awal mengidentifikasi faktor internal dan eksternal. Hasil yang diperoleh berupa strategi pengembangan, antara lain, memperluas WKOPP PPS Bitung, menetapkan kawasan pemukiman nelayan, sinergitas koordinasi antar sektor, penguatan ketersediaan bahan baku industri perikanan, pengelolaan sumber daya ikan yang bertanggung jawab dan berkelanjutan, penguatan kompetensi sumber daya manusia, penegakan hukum, aplikasi teknologi informatika, pengembangan dermaga sesuai standar, dan konsolidasi regulasi.